Penggunaan Media Sosial oleh Anak Usia 13–15 Tahun dalam Mencari dan Memilah Informasi Pembelajaran: Kajian Literatur - Sari, Shesil Puspita; Marlini, Marlini (TSAQOFAH, 2026)
The rapid development of social media has significantly influenced how children and adolescents obtain information, including in learning contexts beyond formal school settings; however, studies that specifically describe how children aged 13–15 use social media to search for and filter learning information in non-formal environments remain limited. This study aimed to provide an in-depth description of how children aged 13–15 utilize social media to seek and screen learning-related information. A descriptive qualitative approach was employed with participants consisting of children residing in the researcher’s neighborhood. Data were collected through semi-structured interviews and observations of social media use activities, supported by relevant literature studies. The findings indicate that social media plays an important role as a source of learning information due to ease of access, speed of information retrieval, and the presentation of engaging visual content. However, children’s ability to evaluate and verify information remains limited; they tend to trust information delivered by content creators or influencers they favor without cross-checking it against other sources. These findings affirm that, although social media supports children’s learning processes, there is a need to strengthen information literacy so that children can be more critical, selective, and responsible in using social media as a source of learning.